The Military Balance 2025. (Routledge, 2025)
The Military Balance has been published since 1959. The 2025 edition provides an open-source assessment of the armed forces and equipment inventories of over 170 countries, with accompanying defence economics data. In addition to detailed country data, The Military Balance includes graphics to illustrate defence personnel, equipment and procurement developments. It assesses important defence issues, by region, including Russia's continuing invasion of Ukraine, the diverse range of ballistic and cruise missiles used by the Houthis, and developments in defence industrial production. The accompanying wallchart focuses on China's armed forces, detailing selected unit locations and assessing the status of important aspects of PLA modernisation. The book draws on the breadth of data in the Military Balance+ online database. The Military Balance and Military Balance+ are indispensable sources of information for those involved in defence and security policymaking, analysis and research.
Keywords: Armed Forces.; Military capital.; Military readiness.; Military capital -- Statistics.; elektronické knihy; electronic books